Tinjauan Yuridis Penegakan Hukum terhadap Pelaku Tindak Pidana Pemerasan dengan Ancaman Kekerasan di Hubungkan Asas Kepastian Hukum (Studi Putusan Nomor 187/Pid.B/2021/Pn.Kwg) - Hendri Gunawan; Deny Guntara; Muhamad Abas (UNES Law Review, 2023)
The problem of crime in this era of development has always been a social problem that is difficult to eradicate or eliminate. The Indonesian National Police (Polri) recorded 276,507 crimes in Indonesia in 2022. This number has increased by 7.3%. The method of coercion used in the criminal act of extortion consists of the perpetrator verbally or in writing threatening, insulting while disclosing secrets. Extortion under the law is regulated in Article 368(1) and Article 369(2). The purpose of this study is to answer the formulation of the problem, namely what are the provisions for law enforcement for the criminal act of extortion with threats based on article 368 of the Criminal Code? And what are the judges' considerations in decision number 187/Pid.B/2021/PN. KWG is related to the principle of legal certainty. The results of the study, first, law enforcement of the criminal act of extortion by threatening under Article 368 paragraph (1) must fulfill the appropriate elements in Article 368. Second, legal certainty in imposing a sentence on the perpetrators of the crime of theft according to Article 368 paragraph (1) of the Criminal Code has been fully implemented and can be proven with the completeness of facts, witnesses and information. This means that the judge's considerations are relevant to the application of article 368 of the Criminal Code.